Shiga toxin-producing Escherichia coli (STEC) O22:H8 isolated from cattle reduces E. coli O157:H7 adherence in vitro and in vivo - Martorelli, Luisina; Albanese, Adriana Andrea; Vilte, Daniel Alejandro; Cantet, Rodolfo Juan Carlos; Bentancor, Adriana Beatriz; Zolezzi, Gisela; Chinen, Isabel; Ibarra, Cristina E.; Rivas, Marta; Mercado, Elsa Cristina; Cataldi, Angel Adrian (2017)
Problem addressed: Shiga toxin-producing Escherichia coli (STEC) are a group of bacteria responsible for foodassociated diseases. Clinical features include a wide range of symptoms such as diarrhea, hemorrhagic colitis and the hemolytic uremic syndrome (HUS), a life-threatening condition. Objective: Our group has observed that animals naturally colonized with STEC strains of unknown serotype were not efficiently colonized with E. coli O157:H7 after experimental infection. In order to assess the basis of the interference, three STEC strains were isolated from STEC persistently-colonized healthy cattle from a dairy farm in Buenos Aires, Argentina. Methods and results: The three isolated strains are E. coli O22:H8 and carry the stx1 and stx2d genes. The activatable activity of Stx2d was demonstrated in vitro. The three strains carry the adhesins iha, ehaA and lpfO113. E. coli O22:H8 formed stronger biofilms in abiotic surface than E. coli O157:H7 (eae+, stx2+) and displayed a more adherent phenotype in vitro towards HeLa cells. Furthermore, when both serotypes were cultured together O22:H8 could reduce O157:H7 adherence in vitro. When calves were intragastrically pre-challenged with 108 CFU of a mixture of the three STEC strains and two days later challenged with the same dose of the strain E. coli O157:H7 438/99, the shedding of the pathogen was significantly reduced. Conclusions: These results suggest that E. coli O22:H8, a serotype rarely associated with human illness, might compete with O157:H7 at the bovine recto-anal junction, making non-O157 carrying-calves less susceptible to O157:H7 colonization and shedding of the bacteria to the environment.